2021
DOI: 10.1111/jvs.13031
|View full text |Cite
|
Sign up to set email alerts
|

Variation in desert shrub foliar pH in relation to drought and salinity in Xinjiang, China

Abstract: Aim Foliar pH, an emerging plant functional trait, plays a key role in plant eco‐physiological processes. However, it remains unclear how foliar pH varies among plants with different preferences concerning soil salinity, and how it responds to drought stress in desert ecosystems. Location Xinjiang, northwestern China (40.24° N to 46.24° N, 80.66° E to 91.33° E). Methods We addressed variation in foliar pH in four desert shrub groups (i.e., euhalophytes, secretohalophytes, pseudohalophytes and glycophytes) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…The effects of soil moisture and salinity on the functional traits of communities in arid zones have been revealed by several studies (Gong et al, 2019;Luo et al, 2021). However, in the present study, soil factors were observed to assume a more mediatory role.…”
Section: Role Of Environmental Factors In the Formation Of Cwm Traitscontrasting
confidence: 58%
“…The effects of soil moisture and salinity on the functional traits of communities in arid zones have been revealed by several studies (Gong et al, 2019;Luo et al, 2021). However, in the present study, soil factors were observed to assume a more mediatory role.…”
Section: Role Of Environmental Factors In the Formation Of Cwm Traitscontrasting
confidence: 58%
“…In this study, the liriodenine alkaloid showed a slight up-regulation in the pH (Figure 4), so the presence of the alkaloid in the cell would not represent a pH imbalance, but rather would help to balance pH. It has been documented that the vacuolar pH is acidic under normal conditions (4.5-6.5; with variation depending on the species and conditions); however, during water stress, it decreases even further [53,54]. Matile [55], and Nowak and Selmar [56], state that alkaloids cross the tonoplast due to differences in pH between the vacuole and the cytoplasm.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, the adjustment of cellular pH is important to maintain resistance to drought. The pH can be increased or decreased by the compounds present in cells, and the pH must be regulated to avoid affecting physiological processes [52,53]. In this study, the liriodenine alkaloid showed a slight up-regulation in the pH (Figure 4), so the presence of the alkaloid in the cell would not represent a pH imbalance, but rather would help to balance pH.…”
Section: Discussionmentioning
confidence: 70%
“…This physiological measure is not usual in agronomy. A first comparative analysis on forty-nine Mediterranean species in different environmental conditions 43 was followed by observations on tree species located along 3300 km of a water gradient 44 and on desert species in China 45 . From a physiological point of view, a lowering of pH can be determined by a stress condition, be it water or heat 43 , such as an excess of UV-A, B 25 or by a reduction of the solar cycle over the years 46 .…”
Section: Journal Of Agronomy Researchmentioning
confidence: 99%